The Effect of Arm Muscle Training Variations and Flexibility on Forehand Clear Ability of Extracurricular Badminton Members At SMPN 1 Adonara Barat - Lein, Yusril Ama; Kurniawan, Rubbi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2024)
Arm muscles greatly determine an athlete's strokes, such as the forehand clear, considering how essential training for arm muscle strength is in a sport, including badminton. Therefore, arm strength training needs to be analyzed in terms of its meaning and purpose as well as the types of training with elements related to supporting further development to achieve performance. Body flexibility is also essential in badminton, as it is the ability to perform movements with a wide range of motion. This study aims to prove the effect of variations in arm muscle training and flexibility on the forehand clear ability of members of the SMPN 1 Adonara Barat badminton extracurricular club. This study is experimental. The design used in accordance with this type of research is a one-group pretest and posttest design. This study involved 14 samples, selected through purposive sampling. The data collection instrument used was a performance test, namely a forehand clear shot test in badminton. Based on the findings and analysis of the research data, it can be concluded that arm muscle strength and flexibility training significantly affect the forehand clear shot performance of members in the SMPN 1 Adonara Barat badminton extracurricular club, as indicated by a t-value (5.303) greater than the critical t-value (2.160) at a 5% significance level, leading to the acceptance of Ha.